O significado do confinamento: compreender como pensam profissionais e familiares - Sa, Izete Pereira de [UNIFESP] (2014)
The aim of this research is to investigate how the professionals who have a performance directed to adolescents in conflict with the law under custody sentence understand the meaning of confinement, and identify the understanding of the relatives of those teenagers regarding deprivation of liberty. This research had been carried through questionnaires and semi-structured interviews with professionals – judges, prosecutors and public defenders, psychologists, social workers and educators – and relatives. Questionnaires and interviews had been analyzed for a better understanding of this issue in the light of other studies to contribute to flesh out this analysis. Accordingly, the research attempted to delve deeper into this kind of confinement and contribute to possible social changes.